Research on mixture motion and combustion chamber of internal combustion engine - Zainal, Helmi Faidzi; Vico Francis, Brandon; Khalid, Amir; Hushim, Mohd Faisal; Ngadiron, Zuraidah (Penerbit UTHM, 2020)
This review paper focuses on the mixture motion into combustion chamber of internal combustion engine. The shape and orientation of the intake port is an important aspect as it defines how the air or fuel/air is delivered to the cylinder and therefore the motion of the fuel/air in the cylinder. Fluid motion into and within the cylinder is known as charge motion and is important due to the influencing turbulence in the cylinder which generally results in faster combustion, which increases combustion efficiency, reduces fuel consumption, reduces knock and pre-ignition in spark ignition engines. The velocity at which the charge enters the cylinder, directing fuel/air towards the spark plug or fuel injector for ignition, the transfer of heat which influences evaporation of the fuel, improving mixing of the fuel/air mixture, and can increase volumetric efficiency, although at the expense of turbulence A main combustion chamber that permits efficient combustion throughout the entire rotational speed range comprising a straight groove extending diametrically from an edge portion of the top surface of a piston and a pair of grooves branching right and left from the straight groove in such a curved manner as to return toward the edge of the surface.